2020
DOI: 10.3389/fphar.2020.00438
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Exerts a Vital Role in the Treatment of Colitis-Associated Cancer by Herbal Medicine

Abstract: Colitis-associated cancer (CAC) is known as inflammatory bowel disease (IBD)-developed colorectal cancer, the pathogenesis of which involves the occurrence of apoptosis. Western drugs clinically applied to CAC are often single-targeted and exert many adverse reactions after long-term administration, so it is urgent to develop new drugs for the treatment of CAC. Herbal medicines commonly have multiple components with multiple targets, and most of them are low-toxicity. Some herbal medicines have been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Based on the theory of traditional Chinese Medicine, effective extraction and compatibility of traditional Chinese Medicine have attracted more and more attention from the medical profession (Bordoloi et al, 2016;Zhang et al, 2018;Mahmoudian-Sani and Asadi-Samani, 2020;Tian et al, 2020). The WXF is a traditional Chinese medicine formula consisted of multiple components, which focuses on dispelling cold, supplementing yangqi, activating blood circulation and clearing blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the theory of traditional Chinese Medicine, effective extraction and compatibility of traditional Chinese Medicine have attracted more and more attention from the medical profession (Bordoloi et al, 2016;Zhang et al, 2018;Mahmoudian-Sani and Asadi-Samani, 2020;Tian et al, 2020). The WXF is a traditional Chinese medicine formula consisted of multiple components, which focuses on dispelling cold, supplementing yangqi, activating blood circulation and clearing blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Animals in each model were randomly divided into 3 groups ( n = 6) as described below: (A) sham group with surgical incision but no adhesion, (B) positive control group with total surgical transection and adhesion receiving normal saline daily, (C) phytosomal curcumin group which is the same as group B except that rats were treated with 25 mg/kg/day curcumin orally [ 23 , 34 ] for either 7 or 21 days in peritoneal or tendon adhesion models, respectively. At the end of the experiments, rats were anesthetized, sacrificed, and tissue samples collected (rapid freezing by liquid nitrogen or stored in 10% formalin) for further assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that resveratrol, a common polyphenol in berries, seems to inhibit the occurrence of tumors by regulating signal transduction mechanisms and programmed cell death ( 73 ). It has been reported that some Chinese herbal medicines containing polyphenols and other active ingredients regulate apoptosis by regulating various signal transduction mechanisms, thus playing a role in preventing CAC ( 87 ).…”
Section: Nutraceuticals For the Treatment Of Ibdmentioning
confidence: 99%